MGNREGA - A Step towards Rural Development - Kumar 2, Sudhir; Verma, Shivani (Journal of Commerce and Trade, 2014)
The National Rural Employment Guarantee Act 2005 (NREGA) is the flagship programme of the UPA Government that directly touches lives of the poor and promotes inclusive growth. NREGA is the first ever law internationally, that guarantees wage employment at an unprecedented scale. NREGA is designed as a safety net to reduce migration by rural poor households in the lean period through a hundred days of guaranteed unskilled manual labour provided when demanded at minimum wage on works focused on water conservation, land development & drought proofing. This study is proposed to examine that how MGNREGA is impacting the lives of millions of people living in rural areas and the citizens living below poverty line. Dr. Jean Drèze, a Belgian born economist, at the Delhi School of Economics, has been a major influence on this project. MGNREGA is an Act to provide a legal guarantee of 100 days of wage employment in a financial year to every rural household whose adult members volunteer to do unskilled manual work. He/she will get the minimum wage rate notified for agricultural labour in the State until the Central Government notifies a minimum wage rate, which in any case shall not be less than Rs. 60 per day. NREGA came into effect on February 2, 2006.